Unusual spin pseudogap behavior in the spin web lattice Cu_{3}TeO_{6} probed by ^{125}Te nuclear magnetic resonance - Seung-Ho Baek; Hyeon Woo Yeo; Jena Park; Kwang-Yong Choi; Bernd Büchner (Physical Review Research, 2021)
We present a ^{125}Te nuclear magnetic resonance (NMR) study in the three-dimensional spin web lattice Cu_{3}TeO_{6} which harbors topological magnons. The ^{125}Te NMR spectra and the Knight-shift K as a function of temperature show a drastic change at T_{S}∼40K much lower than the Néel ordering temperature T_{N}∼61K, providing evidence for the first-order structural phase transition within the magnetically ordered state. Most remarkably, the temperature dependence of the spin-lattice relaxation rate T_{1}^{−1} unravels spin-gap-like magnetic excitations, which sharply sets in at T^{*}∼75K, the temperature well above T_{N}. The spin-gap behavior may be understood by weakly dispersive optical magnon branches of high-energy spin excitations originating from the unique corner-sharing Cu hexagon spin-1/2 network with low coordination number.